Strain-induced trace element mobility in a quartz-sulphide vein system: An example from the ONKALO™ spent nuclear fuel repository (Olkiluoto, SW Finland). (January 2022) - Marchesini, B.; Menegon, L.; Schwarz, G.; Neff, C.; Keresztes Schmidt, P.; Garofalo, P.S.; Hattendorf, B.; Günther, D.; Mattila, J.; Viola, G.
Abstract: This work investigates element mobility and deformation mechanisms in sulphide-bearing quartz veins associated with a strike-slip fault exposed in the ONKALO™ Finnish deep repository for spent nuclear fuel (Olkiluoto Island, southwest Finland). It combines petrography, trace element mapping by Laser Ablation Inductively Coupled Plasma Time-of-Flight Mass Spectrometry (LA-ICP-TOFMS) and Electron Backscattered Diffraction (EBSD) analysis of representative microstructures. The fault core was reactivated by brittle deformation episodes assisted by hydrothermal fluid batches with distinct trace element signatures. LA-ICP-TOFMS element distribution maps and EBSD on sulphides reveal local, syn-deformational intragrain enrichment of primary and secondary elements (i.e., As, Co, Cu, Ag, Sn, Sb, Pb, Se, In, Te). Trace element enrichments occur by a combination of microscale plastic distortions and microfracturing at the reaction fronts. Fluid ingress along microcracks enhanced chemical replacement of pyrite that combined with element diffusion along dislocations and tilt boundaries controlled trace element mobility in sulphides at the small scale. At the scale of the vein system, the competence contrast between inclusions of soft sulphides in the harder host quartz may have favored local fracture nucleation and fluid flow. Highlights: Microstructural analysis and trace element mapping of sulphides. Trace element mobility and chemical replacement of pyrite is promoted by diffusion and microfracture propagation. Sb, Ag and Sn as most effective tracers of intragranular deformation in pyrite.